Lock and load [videorecording (DVD)] - MacDougall, Colin; Shepka, Nathan; Shepka, Nathan; MacPherson, Graeme; MacDonald, Tony (Vision Films, 2023)
Two security guards investigate the disappearance of their good friend, an undercover agent, after his sting operation goes awry. The trail leads to an international arms dealer which puts them in the crosshairs of deadly deals with gun-smuggling terrorists. The clock ticks and the bodies mount as they must take down his infamous organization which is putting the security of the world at stake.